Structure and variscan evolution of Malpica-Lamego ductile shear zone (NW of Iberian Peninsula) - Pamplona, J. (2016)
The Malpica–Lamego ductile shear zone (MLDSZ) is a polyphasic structure developed in the NW of the Iberian Peninsula. The northern sector (NW Spain) of this shear zone is associated with a complex geological history that ranges from earlier Variscan to the emplacement of the Variscan nappes (allochthonous). Variscan intracontinental deformation after the allochthonous nappes emplaced, recognizably strike–slip, explains its spatial and structural continuity from the NW (Malpica, Spain) to the South (Lamego, Portugal). Here we focus on the Variscan development of the MLDSZ and characterize, longitudinally, this crustal megastructure. At the NW tip of the MLDSZ was considered an area (segment 1) with very good exposure of the Variscan intracontinental strike–slip component on outcrops of the coastline. in sequence, we address segment 2, with excellent leff-hand kinematic markers (shearband boudins and folds), on a metapelitic rock series. In the southern most part of the MLDSZ, strike–slip deformation, emplacement of granitic rocks (segment 3 and segment 5), regional structures (segment 4), and secondary manifestations of the southern tip of MLDSZ (segment 6) were studied.